A nation like all others a brief history of American foreign relations - Cohen, Warren I. (Columbia University Press, 2018)
Belief in the United States as a force for good in the world runs deep. Yet an honest consideration reveals a history marred by great crimes and ordinary errors, alongside many achievements and triumphs. In this comprehensive account of American foreign relations from the nation's founding through the present day, the diplomatic historian Warren I. Cohen calls attention to the uses-and abuses-of U.S. international leadership and the noble as well as the exploitative ends that American power has wrought. In A Nation Like All Others, Cohen offers a brisk, argumentative history that confronts the concept of American exceptionalism and decries the lack of moral imagination in American foreign policy. He begins with the foreign policy of colonial and postrevolutionary America, exploring interactions with European powers and Native Americans and the implications of slavery and westward expansion. He then traces the rise of American empire; the nation's choices leading up to and in the wake of the First World War; and World War II and renewed military involvement in foreign affairs. Cohen provides a long history of the Cold War, from its roots under Truman through the Korean and Vietnam Wars to the transformation of the international system under Reagan and Gorbachev. Finally, he surveys America's recent history in the Middle East, with particular attention to the mismanagement of the War on Terror and Abu Ghraib. Written with great depth of knowledge and moral clarity, A Nation Like All Others suggests that an unflinching look at the nation's past is America's best option to shape a better future